Litterfall as a measure of primary production in Mediterranean holm-oak forest - Bellot, J.; Sánchez, J. R.; Lledó, M. J.; Martínez, P.; Escarré, A. (Plant Ecology, 1992)
In this paper we discuss the use of litterfall as a method to measure primary production and its between year relation to climatic fluctuation. Seven years of study in a mediterranean holm-oak forest showed a moderate inter-annual variability of litterfall (C.V. 11°;), while the annual variability of the actual or evapotranspiration was three times higher (C.V. 30/o). Furthermore, the inter- and intra-annual vari- ability of nutrient content in the various fractions are presented in relation to water availability. Monthly and seasonal variability was higher than the annual variability for all analyzed elements.
Keywords: holm-oak; litterfall; litterfall nutrient contents; mediterranean forest; primary production; Quercus ilex; temporal variability